ChemInform Abstract: Copper‐Catalyzed Oxidative Cyclization of 1, 5‐Enynes with Concomitant C—C Bond Cleavage: An Unexpected Access to 3‐Formyl‐1‐indenone Derivatives. Issue 47 (6th November 2014) - Zhang, Jian; Wu, Degui; Chen, Xiaoling; Liu, Yunkui; Xu, Zhenyuan
Abstract A novel water‐induced oxygen‐insertion/β‐carbon elimination via double oxy‐cupration is proposed to be involved in the C—C bond cleavage step.